Nature documentaries and saving nature: Reflections on the new Netflix series Our Planet. Issue 4 (16th September 2019) - Jones, Julia P. G.; Thomas‐Walters, Laura; Rust, Niki A.; Veríssimo, Diogo
Abstract: Netflix recently launched its high‐profile nature documentary Our Planet. Voiced by Sir David Attenborough in English (with Salma Hayek, Penelope Cruz and other Hollywood actors voicing versions simultaneously released in 10 other languages), Netflix are making a clear play for core BBC territory. However, they claim that this is a nature documentary with a difference as it puts the threats facing nature front and center to the narrative. We coded the scripts of Our Planet, and those of three recent Attenborough‐voiced BBC documentaries, to explore the extent to which threats (and conservation action and success) are discussed. The only other series which comes close to the frequency with which these issues are discussed is Blue Planet II, but Our Planet is unique in weaving discussion of these issues throughout all episodes rather than keeping them to a dedicated final episode. However, although Our Planet sounds different to other documentaries, the visuals are very similar. Nature is still mostly shown as pristine, and the presence or impacts of people on the natural world very seldom appear. We discuss the potential consequences of nature documentaries erasing humans from the land/seascape. We also discuss the mechanisms by which nature documentaries may have a positive impact on conservation. Despite links between information provision and behaviour change being complex and uncertain, nature documentaries may, at least in theory, elicit change in a number of ways. They may increase willingness amongst viewers to make personal lifestyle changes, increase support for conservation organizations, and generate positive public attitudes and subsequently social norms towards an issue, making policy change more likely. Netflix is certainly bringing biodiversity and the threats it faces into the mainstream, but the mechanisms by which viewing these representations translates to concrete behaviour change are poorly understood. Increasing interest in robust impact evaluation, integrating qualitative and quantitative methods, means the time is right to explore how both showing nature on screens and talking about the threats it faces, affects people in ways which might, ultimately, contribute to saving it. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.